The characterization of isoflavone content in the Croratian red clover collection - Tucak, Marijana (Array, 2019)
Red clover is a perennial forage crop rich in isoflavones, the bioactive compounds with a positive effect on human and animal health. The aim of the research was to determine a variation in the isoflavone contents in the Croatian red clover collection and to identify the most promising materials to be used in the breeding program for the development of new cultivars for specific purposes. Leaf samples of 29 red clover cultivars/populations (two cultivars, twenty breeding populations, and seven local populations) were collected in a full flowering stage, and the identification and quantification of isoflavones was performed using the HPLC analysis. The most common isoflavones in the red clover cultivars/populations were formononetin and biochanin A. A significant variation among the cultivars/populations in the total and individual isoflavone content was determined. The populations with very high and low contents of both the total and of the individual isoflavones were identified to be used for the breeding purposes in order to develop new forage cultivars, or for specific goals in the pharmaceutical industry.